Class Size and Academic Performance of BISU-MC Engineering Students - Aranjuez, Virgilia; Cayunda, Adelaida Leonor; Torralba, Ryan; Balili, Eric; Polo,; Ann Jelly (JPAIR Multidisciplinary Research, 2011)
The main thrust of the study was to determine the relationship between class size and the academic performance of engineering students of BISU MC during the academic years 2008-2009, 2009- 2010 and 2010-2011. Specifically, the study sought to identify the profile of students’ class size and academic performance, the difference between the academic performance of students belonging to a class size of less than or equal to 50 and a class size of greater than 50, the relationship between class size and the academic performance and the action plan that could be proposed based on the result of the study. The study made use of the descriptive documentary method wherein the academic performance ratings were obtained from the Registrar’s Office. Z-test was used to get the difference between the academic performance of students belonging to a class size of less than 50 and students belonging to a class size of greater than 50. Pearson Product-Moment Correlation Coefficient was used to get the relationship between class size and the academic performance. It was found out that there is no significant difference in the academic performance of students belonging to a class of less than or equal to 50 and students belonging to a class of greater than 50. It was also found out that there was no significant relationship between class size and academic performance of students.